Anomalous extensor tendons of hand: a case report with clinical importance. (Colombia Medica, 2007)
The extensor digitorum muscle of the hand originates from the common extensor origin i.e., from the lateral epicondyle of the humerus and ends in four tendons, one for each digit except for the thumb. This paper reports a case, in which the tendon of the extensor digitorum ended as four tendons to the index, middle, ring and little fingers, but displayed variations in the number of tendons to each finger. Two tendons of extensor digitorum were observed in the ring and the little finger. Such an arrangement of the tendons of the extensor digitorum may have clinical importance. The presence of multiple tendons may also alter the kinematics around the site of attachment to the phalanx. Knowledge of abnormal and normal anatomy of the extensor tendons, may be helpful while performing graft and tendon transfer operations.